PENERAPAN PENDEKATAN KONSTRUKTIVISTIK MELALUI DIALOG UNTUK MENINGKATKAN KEMAMPUAN SISWA DALAM MENGUNGKAPKAN GAGASAN PADA PEMBELAJARAN IPS SEJARAH PADA SISWA KELAS XI IPA-1 SMA NEGERI 2 MAMUJU - Siti Marwah M (Universitas Negeri Makassar, 2021)
The type of action in this research is classroom action research (CAR), which consists of four cycles and each cycle consists of four stages: planning, implementing, observing and reflecting. The type of CAR used is collaborative CAR, in which researchers collaborate with colleagues in carrying out action research according to action procedures including planning, implementing, observing, and reflecting. The research location is SMA Negeri 2 Mamuju, Mamuju Regency. Meanwhile, the research time was semester II, namely January - March 2020. The classes studied were students in class XI-IPA1 SMA Negeri 2 Mamuju with a total of 40 people consisting of 18 boys and 22 girls. The purpose of this research is to improve the learning outcomes of history through the application of constructivist learning, improve students' ability to express ideas, and improve students' ability to dialogue. Data collection techniques used in this study are: Observation, interviews and documentation. Data analysis using Qualitative Description analysis. The learning steps implemented in this study are learning steps with a constructivist approach adopted from Karli (2003: 4), which consists of 4 steps, namely: (1) Apperception, (2) Exploration, (3) Discussion and explanation concept, and (4) Application development. Results from Classroom Action Research: that using a constructivist approach through dialogue can improve students' ability to express ideas in learning history. So it is suggested to history teachers to be able to apply a constructivist approach in dialogue to improve student learning outcomes. Keywords: Constructivist Approach, Dialogue, and Ideas.